New questions on old answers: towards a critical edition of the Answers to the Orthodox of pseudo-Justin - Tóth, P (Oxford University Press, 2014)
The collection of some 150 chapters originally entitled Answers to the Orthodox faithful concerning some necessary questions (Quaestiones et responsiones ad orthodoxos) and attributed to Justin the Martyr is one of the earliest Christian representatives of the late antique genre of question-and-answer literature. The importance of the work consists in that it is the first known example of a new patristic type of erotapokriseis which constitutes an encyclopedic collection of all available secular and religious knowledge of the time. The article presents the first results obtained during the preparation of the new critical edition of this text. Surveying the surprisingly rich manuscript tradition of the Quaestiones, previously known only from four manuscripts, the essay contains a critical assessment not only of the transmission but also of the 500-year-long tradition of scholarship on the text. Contrasting the previous hypotheses on the date, origin, and authorship of the Quaestiones with the evidence of the newly identified manuscripts and the observations made in the course of the textual analysis of the work, it formulates new arguments concerning the problem of the date and authorship of this text.